Strategi Marketing Untuk Menguasai Market Anak Dan Remaja Di Era Digital - Teruna, Dipa; Ardiansyah, Tedy (PRAGMATIS, 2025)
In today's digital era, mastering the children and adolescent market is a strategic challenge for business actors, considering that this group has unique characteristics, both in terms of consumption behavior and digital interaction patterns. Lifestyle changes driven by technology and massive social media penetration make traditional marketing approaches less effective for this segment. The purpose of this study is to formulate a relevant marketing strategy in mastering the children and adolescent market amidst the increasingly strong digitalization. This study uses a qualitative grounded theory approach, involving four key informants consisting of directors and president directors of companies who have experience in handling the children and adolescent market. The data collection process was carried out through in-depth interviews, which were then analyzed using nvivo 12 to facilitate the analysis, the analysis study only focused on comparing two informants, either male or female. The results of this study found six main codes that are important foundations in marketing strategies for this segment, namely: Brand, Channel, Customer, Marketing, Product, and Digital. In addition, 25 supporting variables were identified that contributed to the success of mastering the children and adolescent market, which is also a new finding in this study. It is hoped that these findings can be a practical reference for companies in developing more adaptive and effective strategies in facing the dynamics of the ever-growing digital market.